Use of fumaric acid as a feed additive in quail's nutrition: its effect on growth rate, carcass, nutrient digestibility, digestive enzymes, blood metabolites, and intestinal microbiota - Fayiz M. Reda; Ismail E. Ismail; Adel I. Attia; Ahmed M. Fikry; Eman Khalifa; Mahmoud Alagawany (Poultry Science, 2021)
ABSTRACT: To investigate the effects of dietary fumaric acid (FUA) on performance, carcasses, nutrient digestibility, blood metabolites, digestive enzymes, and cecal microbiota in Japanese quail chicks. Three hundred unsexed Japanese quail (1-wk-old) were randomly assigned to 5 groups. Supplementation of FUA in the diet of Japanese quail chicks exhibited a significant improvement in growth performance through the different experimental periods studied compared with those receiving unsupplemented one. The digestibility of crude protein (CP) and metabolizable energy (ME) were improved with 10 and 15 g/kg FUA, respectively. Apart from lipase enzyme, birds fed 5 and 15 g/kg FUA recorded higher activity of amylase. There were no significant changes among experimental groups on the relative weights of carcass, gizzard, heart, and dressing. Dietary supplementation of FUA at different levels (P> 0.05) increased total protein (TP) and globulin (GLB) concentrations and A/G % compared with control group. A significant (P < 0.01) decrease in plasma low density lipoprotein (LDL) and total cholesterol (TC) levels and increase in high density lipoprotein (HDL) concentrations were observed in chicks fed with FUA containing diets. Immunoglobulin G (IgG) (P = 0.0026) and M (IgM) (P = 0.0007) levels were greater in groups treated with either 10 or 15 g FUA/kg diet. A significant increase in plasma Ca concentration was noticed in chicks received 15 g FUA/ kg compared with the other groups. Quail chicks received diets containing FUA at different levels exhibited reduced cecal count of coliform, E. coli, and Salmonella as compared with control group. In conclusion, supplementation of fumaric acid (especially 15 g/kg diet) in quail chick diets improved their growth, digestibility of nutrients, immune response, antioxidant status, digestive enzyme, and intestinal health.